Molecules and mechanisms that regulate multipolar migration in the intermediate zone - Cooper, Jonathan A. (Frontiers in Cellular Neuroscience, 2014)
Most neurons migrate with an elongated, “bipolar” morphology, extending a long leading process that explores the environment. However, when immature projection neurons enter the intermediate zone of the neocortex they become “multipolar”. Multipolar cells extend and retract cytoplasmic processes in different directions and move erratically - sideways, up and down. Multipolar cells extend axons while they are in the lower half of the intermediate zone. Remarkably, the cells then resume radial migration: they reorient their centrosome and Golgi apparatus towards the pia, transform back to bipolar morphology, and commence locomotion along radial glia fibers. This reorientation implies the existence of directional signals in the intermediate zone that are ignored during the multipolar stage but sensed after axonogenesis. In vivo genetic manipulation has implicated a variety of candidate directional signals, cell surface receptors, and signaling pathways, that may be involved in polarizing multipolar cells and stabilizing a pia-directed leading process for radial migration. Other signals are implicated in starting multipolar migration and triggering axon outgrowth. Here we review the molecules and mechanisms that regulate multipolar migration, and also discuss how multipolar migration affects the orderly arrangement of neurons in layers and columns in the developing neocortex.